Diseksi Spontan Arteri Koroner: Diagnosis dan Manajemen: Coronary Artery Spontaneous Dissection: Diagnosis and Management - Sidhi Laksono; Yogi Subandra (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Spontaneous coronary artery dissection (SCAD) is one of the rare causes of ACS cases but is increasing in incidence in young women with low cardiovascular risk assessment. In addition, SCAD has risk factors for pregnancy and fibromuscular dysplasia. Establishing the diagnosis of SCAD by coronary angiography is a challenge because the characteristics of SCAD are similar to other causes of ACS and often missed. It is hoped that SCAD can be a research concern to support diagnosis and management to produce better outcomes. Keywords: coronary artery spontaneous dissection, diagnosis, management, acute coronary syndrome Abstrak Diseksi spontan arteri koroner (Spontaneous Coronary Artery Dissection: SCAD) salah satu penyebab kasus SKA yang jarang tetapi meningkat insidensi pada wanita muda dengan penilaian risiko kardivaskular rendah. Selain itu SCAD memiliki faktor risiko terhadap kehamilan, dan penyakit fibromuscular dysplasia. Penegakan diagnosis SCAD dengan angiografi koroner menjadi tantangan dikarenakan karakteristik SCAD yang mirip dengan penyebab ACS lainnya dan sering kali terlewat. Diharapkan SCAD dapat menjadi perhatian penelitiaan untuk mendukung penegakan diagnosis dan manajemen guna menghasilkan keluaran lebih baik. Kata Kunci: diseksi spontan arteri koroner, diagnosis, manajemen, sindroma korone akut